Recurrent Motifs: The Fiction of Time in José Manuel Caballero Bonald’s Poetry (Castilla. Estudios de Literatura, 2012)
Time, memory and forgetfulness are recurring motifs in the work of the poets of the generation of the 50’s or generación del medio siglo. This article focuses on José Manuel Caballero Bonald’s personal revision of the concept of time, one of the most universal poetic themes. The poet takes his rhetoric from the Baroque tradition to re-visit ideas of time and provide a reinterpretation that contrasts sharply with that of contemporary poets while laying down a clear thread of intertextuality with the literary culture of the past. For his meditation on time, the poet's legacy results in a unique amalgam of Borges’ motifs and the Baroque worldview. From Quevedo’s intertext, the author’s new Baroque style blends poetic culteranismo and conceptismo with lexical precision to result in a lyrical universe that reconciles opposites, a poetic writing more nourished by knowledge than by experience, and a form of expression strongly embedded in the formal and conceptual systems of the Baroque.